# Boolean Algebra Proofs Postulates and Theorems (Part 1)

Boolean Algebra Postulates and Theorems (Part 1):

First familiarize with truth tables so it’ll be easier to understand.

### x + 0 = x

here only two possible states of x, 0 remains constant

```x = 0
x = 1
```

So,

```false OR false is always false
0 + 0 = 0
true OR false is always true
1 + 0 = 1
```

So, from this we can see whatever the value of x is, the output is always equal to x.

### x . 1 = x

here only two possible states of x, 1 remains constant

```x = 0
x = 1
```

So,

```false AND true is always false
0 . 1 = 0
true AND true is always true
1 . 1 = 1
```

So, from this we can see whatever the value of x is, the output is always equal to x.

### x + 1 = 1

here only two possible states of x, 1 remains constant

```x = 0
x = 1
```

So,

```false OR true is always true
0 + 1 = 1
true OR true is always true
1 + 1 = 1
```

So, from this we can see no matter the value of x, OR with 1 (true) always gives a 1 (true) value.

### x . 0 = 0

here only two possible states of x, 0 remains constant

```x = 0
x = 1
```

So,

```false AND false is always false
0 . 0 = 0
true AND false is always false
1 . 0 = 0
```

So, from this we can see no matter the value of x, AND with 0 (false) always gives a 0 (false) value.

### x + x’ = 1

```x = 0, x' = 1
x = 1, x' = 0
```

So,

```false OR true is always true
0 + 1 = 1
true OR false is always true
1 + 0 = 1
```

### x . x’ = 0

```x = 0, x' = 1
x = 1, x' = 0
```

So,

```false AND true is always false
0 . 1 = 0
true AND false is always false
1 . 0 = 0
```

### x + x = x

```x = 0, x = 0
x = 1, x = 1
```

So,

```false OR false is always false
0 . 0 = 0
true OR true is always true
1 . 1 = 1
```

So, we can whatever the value of x is, that is our output.

### x . x = x

```x = 0, x = 0
x = 1, x = 1
```

So,

```false AND false is always false
0 . 0 = 0
true AND true is always true
1 . 1 = 1
```

So, again we can whatever the value of x is, that is our output.

### (x’)’ = x

```x = 0, x' = 1, (x')' = 0
x = 1, x' = 0, (x')' = 1
```

So, we can see complementing twice gives the original value.